PEMANFAATAN SUMBERDAYA ALAM OLEH MASYARAKAT ENCLAVE DI ZONA TRADISIONAL TAMAN NASIONAL BROMO TENGGER SEMERU - , GILIG LILO SAMADYO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Taman Nasional Bromo Tengger Semeru is a national park in which the management applies the traditional zone surrounding the area of enclave society. The traditional zone is applied in order to give limitations to the enclave society in utilizing the natural resources. This research is aimed to find out the system or the structure of the utilization of natural resources by the enclave society and its suitability with the main function of the traditional zone Taman Nasional Bromo Tengger Semeru. The research methods used in this research are participative observation technique, in depth interview technique, and document collection technique. The sampling technique used in this research is the snowball sampling, started with purposive sampling. The first sample is selected using the key informant. The result of the research shows that the utilization natural resources done by the enclave society in traditional zone Taman Nasional Bromo Tengger Semeru is divided into two: the utilization of the land and the utilization of the non-land. However, the utilization of the natural resources done by enclave society is not appropriate with respect to the rules and the main function of traditional zone of the national park. The utilization can also potentially lead to the deforestation, land clearing, and the separation of the national park area.